2020
DOI: 10.5114/ada.2019.83629
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and severity of fatigue in psoriasis and psoriatic arthritis

Abstract: Introduction: Fatigue is an important and underrated symptom of many chronic diseases. Aim: The evaluation of incidence and severity of fatigue as well as the influence of selected factors on fatigue in patients with psoriasis and psoriatic arthritis (PsA). Material and methods: The study included 60 patients with PsA, 58 patients with psoriasis and 61 persons in the control group aged 35-70 years. Assessment of fatigue was conducted using a fatigue subscale from the FACIT-F questionnaire. Severity of skin les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Well-known factors that can affect response to PsA treatment include female sex and pre-existing obesity. These observations may relate to females, who have longer PsA disease duration, higher BMI, higher disease severity scores and increased central sensitisation compared with males,32–34 reporting more severe fatigue and poorer physical function than males 32 35–37. Consistent with these predisposing factors, a numerically smaller proportion of females than males achieved an MDA response at weeks 24 and 52, though a similar trend in greater achievement of MDA response at weeks 24 and 52 with guselkumab versus placebo was seen for both the Q4W and Q8W guselkumab dosing regimens in both males and females.…”
Section: Discussionmentioning
confidence: 87%
“…Well-known factors that can affect response to PsA treatment include female sex and pre-existing obesity. These observations may relate to females, who have longer PsA disease duration, higher BMI, higher disease severity scores and increased central sensitisation compared with males,32–34 reporting more severe fatigue and poorer physical function than males 32 35–37. Consistent with these predisposing factors, a numerically smaller proportion of females than males achieved an MDA response at weeks 24 and 52, though a similar trend in greater achievement of MDA response at weeks 24 and 52 with guselkumab versus placebo was seen for both the Q4W and Q8W guselkumab dosing regimens in both males and females.…”
Section: Discussionmentioning
confidence: 87%
“…In different studies, fatigue was more frequently reported among patients with PsA than patients with cutaneous psoriasis alone and, according to that, more than half of our sample suffered from moderate to severe fatigue (27,28). Depression is a recognized but understudied comorbidity in patients with PsA, and according to the PHQ-9 questionnaire, 40% of the subjects had moderate to very severe depression.…”
Section: Discussionmentioning
confidence: 51%
“…In different studies, fatigue was more frequently reported among patients with PsA than patients with cutaneous psoriasis alone and, according to that, more than half of our sample suffered from moderate to severe fatigue ( 27 , 28 ).…”
Section: Discussionmentioning
confidence: 54%